2003
DOI: 10.1007/s00259-003-1144-y
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis and follow-up of aortitis with [18F]FDG PET and MRI

Abstract: The aim of this prospective study was to compare fluorine-18 fluorodeoxyglucose ([(18)F]FDG) positron emission tomography (PET) with magnetic resonance imaging (MRI) in patients with early aortitis, at the time of initial diagnosis and during immunosuppressive therapy. The study population consisted of 15 patients (nine females and six males; median age 62 years, range 26-76 years) who presented with fever of unknown origin or an elevated erythrocyte sedimentation rate or elevated C-reactive protein and who sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
197
1
24

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(237 citation statements)
references
References 12 publications
7
197
1
24
Order By: Relevance
“…PET imaging with [ 18 F]FDG can detect tissue inflammation in a variety of different clinical settings (28)(29)(30), and quantification of inflammation using PET has been applied to the lungs (31,32). All studies to date suggest that during acute inflammation, increases in lung [ Glucose Metabolic Rate Radioactivity Ratio (ml blood/ml lung/min) (ml blood/ml lung) (ml blood/ml lung/min) (mg glucose/100 ml lung/min) (ml blood/ml lung) Normal subjects (n ϭ 6) 0.0007 Ϯ 0. parenchymal cells likely also contribute significantly to the PET imaging signal (36).…”
Section: Discussionmentioning
confidence: 99%
“…PET imaging with [ 18 F]FDG can detect tissue inflammation in a variety of different clinical settings (28)(29)(30), and quantification of inflammation using PET has been applied to the lungs (31,32). All studies to date suggest that during acute inflammation, increases in lung [ Glucose Metabolic Rate Radioactivity Ratio (ml blood/ml lung/min) (ml blood/ml lung) (ml blood/ml lung/min) (mg glucose/100 ml lung/min) (ml blood/ml lung) Normal subjects (n ϭ 6) 0.0007 Ϯ 0. parenchymal cells likely also contribute significantly to the PET imaging signal (36).…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions, it can detect occult areas of vascular inflammation and thus demonstrate the full extent and distribution of vasculitis (6,10,11); further- more, in Takayasu's arteritis, 18 F-FDG-PET proved to be more reliable than MRI in monitoring disease activity (10).…”
Section: Discussionmentioning
confidence: 99%
“…This modality estimates both the degree and site of inflammation. Meller et al 44 reported that FDG-PET is more reliable than MRI in the follow-up of TA patients in limited situations. FDG-PET imaging is recommended for diagnosis of TA or its recurrence, especially in the presence of negative inflammatory markers; However, it is not economical as a routine procedure.…”
Section: -Related Diseases Ergotismmentioning
confidence: 99%